IP-centric control and management of optical transport networks. - Bernstein, G.M (IEEE Communications magazine)
Previous techniques for the management and control of optical transport networks are proving inadequate in today's rapidly evolving multivendor environments. This article examines the issues and challenges involved in developing a standardized optical network control plane. The control of optical transport networks is decomposed into provisioning models, a circuit provisioning process based on signaling, a neighbor and service discovery process, and a topology and resource discovery process. Unique properties and challenges of optical transport networks are explained in the context of these functions